GreenUp: A Decentralized System for Making Sleeping Machines Available - Sen, Siddhartha; Lorch, Jay; Hughes, Richard; Garcia, Carlos; Zill, Brian; Cordeiro, Weverton; Padhye, Jitu (2012)
Large enterprises can save significant energy and money by putting idle desktop machines to sleep. Many systems that let desktops sleep and wake them on demand have been proposed, but enterprise IT departments refuse to deploy them because they require special hardware, disruptive virtualization technology, or dedicated per-subnet proxies, none of which are cost-effective. In response, we devised GreenUp, a minimal software-only system that allows any machine to act as a proxy for other sleeping machines in its subnet. To achieve this, GreenUp uses novel distributed techniques that spread load through randomization, efficiently synchronize state within a subnet, and maintain a minimum number of proxies despite the potential for correlated sleep times. In this paper, we present the details of GreenUp's design as well as a theoretical analysis demonstrating its correctness and efficiency, using empirically-derived models where appropriate. We also present results and lessons from a seven-month live deployment on over 100 machines; a larger deployment on 1,100 machines is currently ongoing.